Development of digital financial instruments and their use in the activities of entities of the pharmaceutical industry of Ukraine - Manoylenko, Oleksandr; Kuznetsova, Svitlana (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The pharmaceutical industry of Ukraine is an important component of its economy and the health of its population. At all stages of its development, it was and remains the centre of innovations, where the scientifi c and technological potential of the region is concentrated. Theoretical and practical aspects of the development of innovative digital fi nancial instruments and fi nancial support were investigated and on their basis the activities of enterprises of the pharmaceutical industry in the conditions of the digital economy and electronic commerce as the most perspective segment of the modern market in the conditions of restrictions on direct contacts and the movement of people due to measures to combat the pandemic have been studied, military actions and security of people have been studied. It was determined that fi nancial instruments can be conditionally divided into traditional and digital. They have similar content, functions, and features, however, they have diff erent spheres of manifestation, advantages, disadvantages, and risks. At the same time, the implementation of digital fi nancial instruments allows to signifi cantly save the time of entrepreneurs and customers or services; it also saves cash; simplifi es administration and, as a result, it increases the profi tability of enterprises, in particular, the pharmaceutical industry. The study shows wide opportunities for the development and application of embedded fi nance in the pharmaceutical sphere with the aim of increasing business profi tability by saving time, premises and other means of providing and implementing fi nancial activities; and economic benefi ts to consumers and partners; optimization of business processes and management of activities in general; promotion of innovation, investment and integration processes.
Keywords: digital financial instruments; embedded finance; digital economy; pharmaceutical industry; business technologies; financial results